Vigilar y programar: sobre la dimensión política del software - Jordán, Rubén (2021)
This article explores the pharmacological character of technology in the light of the anonymous internet browsing free software case and its political potential. It is contended that software, which is at the foundation of the neoliberal surveillance and psychopolitical control system depicted by Byung-Chul Han, may be at the same time, when implemented in open-source programs that hide our digital fingerprint, a tool for resistance and emancipation. This is due to the fact that such implementation attacks the fundamental principles of the dataist domination logic: transparency and predictability.